Conflicts in Mangrove-based Tourism in Kulon Progo, Indonesia - Aji, Khusnul Bayu; Pakan, Sarani Pitor (Jurnal Pariwisata Terapan, 2023)
It has become increasingly common to develop the ecosystem of mangrove into a tourism product. Such trend is also seen in Indonesia, including the coastal part of Kulon Progo, DI Yogyakarta Province. However, as the case of other tourism niches, the development of mangrove-based tourism more often than not is facing myriad challenges. This brief research paper aims to identify the challenges related to mangrove-based tourism development, by using Kulon Progo mangrove areas as a case study. Based on data gathered from observation, GIS mapping, semi-structured interviewing, and literature study, this research finds that conflicts have been occurring in the development process of mangrove-based tourism in Kulon Progo. Conflicts related to local-to-local relations, intergroup competition, destination management, and tourism income distribution have been hindering the tourism development process. Given the main findings, potential conflict resolutions may include stakeholder collaboration, product innovation, and paradigmatic shift to shy away from mass tourism development model. This research contributes to the body of literature on mangrove tourism by adding the issue of tourism conflicts into the debate.